2018
DOI: 10.1049/mnl.2017.0326
|View full text |Cite
|
Sign up to set email alerts
|

Deep insight into linearity and NQS parameters of tunnel FET with emphasis on lateral straggle

Abstract: Tunnel field-effect transistor (TFET) is considered to have superior device performance compared with DG-metal-oxide-semiconductor FET in terms of reduced off-state current and lower subthreshold swing. However, performance of a device solely depends on the accuracy in the fabrication process. This work presents a systematic methodology in small-signal-radio-frequency (RF) and linearity domain to analyse the effect of variation in lateral straggle caused by the variation tilt angle during ion implantation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Table 2 shows the Comparison of the linearity parameters of the proposed device (having L D = 20 nm, L C = 20 nm & GWF = 4.2 eV) with the data already reported. Here IIP3 & VIP3 of the proposed device are higher, and IMD3 is lower than the other devices [30][31][32] with the lower value of VIP2. Thus the proposed device Inner-Gated NWTFET [36], Dual Material Gate Heterogeneous Dielectric Vertical TFET [37], GAA Nanowire FET [38], Multi Bridge channel FET [39] and Nanosheet FET [40] are compared with proposed device Electrostatically doped Vertical Nanowire TFET & it is observed that E-VNWTFET is having better I ON /I OFF, Lower DIBL and better subthreshold slope than most of the devices.…”
Section: Characteristics Variation Of E-vnwtfet For Various Scaled Di...mentioning
confidence: 72%
See 1 more Smart Citation
“…Table 2 shows the Comparison of the linearity parameters of the proposed device (having L D = 20 nm, L C = 20 nm & GWF = 4.2 eV) with the data already reported. Here IIP3 & VIP3 of the proposed device are higher, and IMD3 is lower than the other devices [30][31][32] with the lower value of VIP2. Thus the proposed device Inner-Gated NWTFET [36], Dual Material Gate Heterogeneous Dielectric Vertical TFET [37], GAA Nanowire FET [38], Multi Bridge channel FET [39] and Nanosheet FET [40] are compared with proposed device Electrostatically doped Vertical Nanowire TFET & it is observed that E-VNWTFET is having better I ON /I OFF, Lower DIBL and better subthreshold slope than most of the devices.…”
Section: Characteristics Variation Of E-vnwtfet For Various Scaled Di...mentioning
confidence: 72%
“…The device dimensions are scaled down, but due to the scaling the output signal can have noise; that is why it is important to analyse the linearity parameters VIP2, VIP3, IIP3 & IMD3 [29][30][31][32][33][34] of the device. Figures 10(a) & (b) shows the variation VIP2/VIP3 for V GS respectively.…”
Section: Characteristics Variation Of E-vnwtfet For Various Scaled Di...mentioning
confidence: 99%
“…Koley et al highlighted that RF/analog parameters of symmetric and asymmetric DG MOSFET is improved with increased in σ 26 . It is also reported that RF/analog and linearity behavior of DG TFET is suppressed with rise in σ value 27,28 . Over course of time, analysis on effect of σ on RF/analog characteristic are presented in gate modulated 29 and hetero‐stacked TFETs 30 .…”
Section: Introductionmentioning
confidence: 99%
“…26 It is also reported that RF/analog and linearity behavior of DG TFET is suppressed with rise in σ value. 27,28 Over course of time, analysis on effect of σ on RF/analog characteristic are presented in gate modulated 29 and hetero-stacked TFETs. 30 Recently, the effect of source/drain gradient for the variation in lateral straggle parameter in terms of DC and RF performance is highlighted in Ge epitaxial DG TFET.…”
Section: Introductionmentioning
confidence: 99%
“…A TFET can deliver the SS values smaller than that of a conventional MOSFET ( 60 mV/decade at room temperature) [1]. In the recent past, several research efforts have been made to improve the performance of TFETs [5–13]. Despite the excellent switching performance and reduced InormalOFF, the TFETs suffer from low ON‐state current (InormalON) which restricts the use of TFETs for commercial applications.…”
Section: Introductionmentioning
confidence: 99%